Creativity and innovation in business and beyond : social science perspectives and policy implications - Chan, Janet; Mann, Leon (Routledge studies in innovation, organization and technology, 2011)
1. Introduction : creativity and innovation -- 2. National innovation systems and creativity -- 3. Innovation and creativity in industry and the service sectors -- 4. Space, place and innovation -- 5. Historical approaches to creativity and innovation -- 6. Economic approaches to understanding and promoting innovation -- 7. Creativity and innovation: a legal perspective -- 8. Promoting creativity and innovation through law -- 9. Towards a sociology of creativity -- 10. Social psychology of creativity and innovation -- 11. Creativity and innovation management : play?s the thing -- 12. Inducing and disciplining creativity in organisations under escalating complexity -- 13. Creativity and innovation : an educational perspective -- 14. The psychology of creativity and its educational consequences -- 15. Creativity meets innovation : examining relationships and pathways -- 16. Creativity and innovation : principles and policy implications